Diadromy in a large tropical river, the Mekong: more common than assumed, with greater implications for management. Issue 1 (2nd January 2023) - Vu, An V.; Baumgartner, Lee J.; Mallen-Cooper, Martin; Howitt, Julia A.; Robinson, Wayne A.; So, Nam; Cowx, Ian G.
Abstract: Diadromous fishes, those that migrate between fresh and marine waters, are among the most vulnerable species to river infrastructural development. These fish need to move between fresh water and the sea, so any obstruction to migration can block access to critical habitat areas. The Lower Mekong Basin (LMB) is experiencing an unprecedented boom in river development, with many dams and irrigation schemes being installed. Although general patterns of fish migration are known in the LMB, there is relatively little information on diadromous fish migration, so the overall impacts of river development on their population status is likely underestimated for many species. In this study, we reviewed the available information for over one thousand Mekong fish species to identify evidence for diadromy. Our results found that diadromy is likely a more common life history trait in the LMB than previously assumed. For instance, 61 of the 1136 Mekong fish species assessed exhibit diadromous traits (44 amphidromous species, 9 anadromous species, and 8 catadromous species). Many of these species are known to migrate relatively long distances, connecting with the Mekong estuary to some extent to complete their life cycles. Based on routine fish catch monitoring data, these suspected diadromous fishes contributed around 3% to the total catch across the basin and included a number of endemic species of significant economic value. Riverine development must therefore proceed in a balanced manner to protect diadromous species diversity and associated fisheries resources, whilst also meeting food and energy demands in the region.